Genetic Alterations of Periampullary and Pancreatic Ductal Adenocarcinoma: An Overview - Sikdar, Nilabja; Saha, Gourab; Dutta, Ashmita; Ghosh, Shibajyoti; Shrikhande, Shailesh V.; Banerjee, Sudeep (Current Genomics, 2018)
Pancreatic Ductal AdenoCarcinoma (PDAC) is one of the most lethal malignancies of all solid cancers. Precancerous lesions for PDAC include PanIN, IPMNs and MCNs. PDAC has a poor prognosis with a 5-year survival of approximately 6%. Whereas Periampulary AdenoCarcinoma (PAC) having four anatomic subtypes, pancreatic, Common Bile Duct (CBD), ampullary and duodenum shows relative better prognosis. The highest incidence of PDAC has been reported with black with respect to white population. Similarly, incidence rate of PAC also differs with different ethnic populations. Several lifestyle, environmental and occupational exposures including long-term diabetes, obesity, and smoking, have been linked to PDAC, however, for PAC the causal risk factors were poorly described. It is now clear that PDAC and PAC are a multi-stage process resulting from the accumulation of genomic alterations in the somatic DNA of normal cells as well as inherited mutations. Approximately 10% of PDAC have a familial inheritance. Germline mutations in CDKN2A, BRCA2, STK11, PALB2, PRSS1, etc., as well as certain syndromes have been well associated with predisposition to PDAC. KRAS, CDKN2A, TP53 and SMAD4 are the 4 “mountains” (high-frequency driver genes) which have been known to earliest somatic alterations for PDAC while relatively less frequent in PAC. Our understanding of the molecular carcinogenesis has improved in the last few years due to extensive research on PDAC which was not well explored in case of PAC. The genetic alterations that have been identified in PDAC and different subgroups of PAC are important implications for the development of genetic screening test, early diagnosis, and prognostic genetic markers. The present review will provide a brief overview of the incidence and prevalence of PDAC and PAC, mainly, increased risk in India, the several kinds of risk factors associated with the diseases as well as required genetic alterations for disease initiation and progression.
Keywords: Pancreatic ductal adenocarcinoma